Discrete Sequence Production With and Without a Pause: The Role of Cortex, Basal Ganglia and Cerebellum - Jouen, Anne-Lise; Verwey, Willem B.; Van Der Helden, Jurjen; Scheiber, Christian; Neveu, Remi; Dominey, Peter F.; Ventre-Dominey, Jocelyne (Frontiers in Human Neuroscience, 2013)
Our sensorimotor experience unfolds in sequences over time. We hypothesize that the processing of movement sequences with and without a temporal pause will recruit distinct but cooperating neural processes, including cortico-striatal and cortico-cerebellar networks. We thus compare neural activity during sequence learning in the presence and absence of this pause. Young volunteer participants learned sensorimotor sequences using the discrete sequence production (DSP) task, with Pause, No-Pause and Control sequences of four elements in an event related fMRI protocol. The No-Pause and Pause sequences involved a more complex sequential structure than the Control sequence, while the Pause sequences involved insertion of a temporal pause, relative to the No-Pause sequence. The Pause vs. No-Pause contrast revealed extensive fronto-parietal, striatal, thalamic and cerebellar activations, preferentially for the Pause sequences. ROI analysis indicated that the cerebellum displays an early activation that was attenuated over successive runs, and a significant preference for Pause sequences when compared with caudate. These data support the hypothesis that a cortico-cerebellar circuit plays a specific role in the initial processing of temporal structure, while the basal ganglia play a more general role in acquiring the serial response order of the sequence.